2017
DOI: 10.18196/hi.61106
|View full text |Cite
|
Sign up to set email alerts
|

Labour Migration from Indonesia to South Korea: Challenges in Maximizing Potentials

Abstract: Labour migration is one of the forms of international migration, which according to Martin (2013) is motivated by demographic and economic inequalities, as well as communication, transportation and human rights revolutions (Martin, 2013). Martin pointed out how the high demographic growth tends to occur in 170 poorer countries, while the demography in wealthier countries tends to grow slower. Economically, wealth is more concentrated in countries with smaller population. This is believed to be the reasons for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
3
0
1
Order By: Relevance
“…Berbeda dengan push strategy dan pull strategy, pass strategy cenderung pada aspek "mempengaruhi". Philip Kotler (2002: 646) dalam (Yazid, 2017) mendefinisikan pass strategy untuk menciptakan citra publik yang ditimbulkan melalui kegiatan dan partisipasi, dalam hal ini adalah kegiatan masyarakat atau sosial. Biasanya, bentuk kepeduliannya ini menangkut masalah-masalah kondisi sosial dan lingkungan hidup.…”
Section: Model Strategi Komunikasiunclassified
“…Berbeda dengan push strategy dan pull strategy, pass strategy cenderung pada aspek "mempengaruhi". Philip Kotler (2002: 646) dalam (Yazid, 2017) mendefinisikan pass strategy untuk menciptakan citra publik yang ditimbulkan melalui kegiatan dan partisipasi, dalam hal ini adalah kegiatan masyarakat atau sosial. Biasanya, bentuk kepeduliannya ini menangkut masalah-masalah kondisi sosial dan lingkungan hidup.…”
Section: Model Strategi Komunikasiunclassified
“…Along with security and the quality of education, it was one of the main driving factors for the Wamena people to migrate to Jayapura. In general, migration occurred because of various economic, social and cultural, environmental and political considerations (Yazid, 2017;Taryono et al, 2009). Furthermore, Elfranita et al (2013) have shown that dissatisfaction with the area of origin encourages individuals and families to migrate.…”
Section: Driving and Pulling Factors To Migratementioning
confidence: 99%
“…Some of the push model & pull model studies are analyze international migrant workers. Then, academic articles about Indonesian migrant workers to Malaysia (Djafar & Hassan, 2012); Case study of Indonesian migrant workers to South Korea (Yazid, 2017); Rural case studies to urban areas in China (Hare, 1999); from or to South Africa (Rasool et al, 2012); and from or to India (Kainth, 2010) explained push and pull factors as determinant points for migrants on why they did migration.…”
Section: Introductionmentioning
confidence: 99%